Pola Kedisiplinan Pakaian Pada Siswa Dalam Kajian Pendidikan Karakter Di SDN 3 Piji Kabupaten Kudus - ., Della Ayu Puspita; ., Liftiya Ayu Lestari; ., Andre Adiatma Hafis; ., Cynthia Carla Ika Santoso; ., Nur Fajrie (CV. ITTC INDONESIA, 2023)
This study aims to describe situations or incidents regarding the disciplinary pattern of clothing on students in character education studies at SDN 3 Piji, Kudus Regency. This study uses a narrative research method with a qualitative approach. Data collection techniques used in this study were interviews, observation, documentation, and literature studies. The results of the study show that students at SDN 3 Piji are disciplined in complying with the dress code applied by the school, this becomes a support in improving student character.